2020
DOI: 10.1001/jamanetworkopen.2020.20671
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Respiratory Symptoms Among Youth e-Cigarette Users

Abstract: IMPORTANCE Use of e-cigarettes (ECs) among youths has increased in recent years. e-Cigarette aerosol contains chemical constituents, such as diacetyl or benzaldehyde, which are known to affect the respiratory system. OBJECTIVE To examine the association between EC use and self-reported wheezing in a cohort of US adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 40 publications
(107 reference statements)
1
15
1
Order By: Relevance
“…Overall, respiratory symptoms (cough, phlegm production, or shortness of breath) were reported in approximately 28% of the sample, a much higher frequency than those symptoms previously reported in another research. (9)(10)(11) Compared to never users, e-cigarette use was associated with up to 50% increased odds of respiratory symptoms; the highest odds were found for those using some day, followed by former users of e-cigarette.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, respiratory symptoms (cough, phlegm production, or shortness of breath) were reported in approximately 28% of the sample, a much higher frequency than those symptoms previously reported in another research. (9)(10)(11) Compared to never users, e-cigarette use was associated with up to 50% increased odds of respiratory symptoms; the highest odds were found for those using some day, followed by former users of e-cigarette.…”
Section: Discussionmentioning
confidence: 99%
“…E-cigarette is also associated with wheezing, chronic cough, phlegm, or bronchitis in children and adults. (9)(10)(11). The results of a recently published systematic review estimated that the pooled OR associated with e-cigarette use for asthma was 1.39 (95% confidence interval (CI) 1.28-1.51) and for COPD was 1.49 (95% CI 1.36-1.65) (12).…”
mentioning
confidence: 99%
“…A survey conducted on 3,488 schoolchildren aged 6-17 years in Switzerland investigated the association between active smoking of CC, EC and shishas and current respiratory symptoms, and found that dyspnea and wheeze were more widespread among frequent smokers, i.e., those who smoked at least once/week (30 and 12%, respectively), and occasional smokers (22 and 13%) [1.56-4.08] for >3 days), compared with non-EC users (p for trend = 0.001) (24). More recently, in a cohort study of 7,049 adolescents, the association of EC use alone with wheezing in the past 12 months proved not to be significant (25). Overall, it should be pointed out that data from the aforementioned studies are self-reported and may be subjected to recall bias.…”
Section: Post-natal Respiratory Effects Of Ec Exposure In Childhoodmentioning
confidence: 99%
“…Accordingly, some of the most common questions during the COVID-19 epidemic were whether e-cigarette use increased the risk for being infected with SARS-CoV-2 and whether vaping increased severity and mortality. Although these questions have not yet been answered to our satisfaction in human subjects, the data are most supportive of e-cigarette users having more respiratory symptoms even before viral infections, [40][41][42][43] with potentially increased symptoms in the setting of COVID-19. 44 One national cross-sectional survey of adolescents and young adults (aged 13-24 years) performed in May 2020 found that both e-cigarette users and dual e-cigarette and cigarette users were more likely to receive a diagnosis of COVID-19 compared with nonusers, and ever-users of e-cigarettes were five times more likely to test positive (OR ¼ 5.05; 95% CI, 1.82-13.96), 45 although the authors noted that there were likely both immunologic and social contributors to positive testing among e-cigarette-using young adults.…”
Section: Cellular Immunomodulationmentioning
confidence: 99%